Risiko Usaha dan Strategi Pengembangan Agroindustri Olahan Berbahan Dasar Ikan “UD Diana Indah” di Desa Gelung Kecamatan Panarukan Kabupaten situbondo - Primasari Puspitaningrum; Ati Kusmiati (UPT Penerbitan Universitas Jember, 2018)
Fisheries sub-sector is one of the sub-sectors that has a strategic role innational development because the potential of Indonesia's natural resources as the largestmaritime country with fishery resources that the number is relatively large and scatteredalmost throughout the Indoneisa region. The research is aimed to know 1) Income of agroindustry